Dangling carboxylic-acid functionality in a fish-bone-shaped 2D framework as a hydrogen-bond-donating catalyst in Friedel–Crafts alkylation. Issue 33 (4th April 2023) - Seal, Nilanjan; Neogi, Subhadip
Abstract : A fish-bone-shaped 2D MOF with oppositely faced pendent –COOH groups demonstrates the first-ever carboxylic-acid-driven Friedel–Crafts alkylation where control experiments validate two-point H-bonding. Abstract : A two-dimensional, layer-stacked metal-organic framework (MOF) with a dangling acid functionality was developed as the first-ever example of carboxylic-acid-catalysed Friedel–Crafts alkylation with high reusability. Contrary to conventional hydrogen-bond-donating catalysis, a pair of oppositely oriented –COOH moieties acted as potential hydrogen-bonding sites, and efficiently worked for electronically assorted substrates. Control experiments including juxtaposing the performances of a post-metalated MOF and an unfunctionalized analogue explicitly authenticated the carboxylic-acid-mediated catalytic route.